Efektivitas Metode 5 S terhadap Respon Nyeri pada Bayi Usia 2-6 Bulan saat Imunisasi Pentavalen - Dewi Astuti Pasaribu; Septian Mixrova Sebayang (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2021)
Pentavalent immunization is an immunization developed from a combination of vaccines so that there are eight antigens that can be given to children, namely Hepatitis B, BCG, Oral Polio, Diphtheria, Pertussis, Tetanus, Hib and Measles. The act of immunization can cause pain in babies, so that the baby becomes fussy. The aim of this study is to determine the effectiveness of the 5 S Method (Swaddling, Side / Stomach Position, Shushing, Swinging, Sucking) on Pain Response in Infants aged 2-6 Months during Immunization. Pentavalent. The design of this research is experimental research with the design of Post Test Only Control Group Design. The total sample in this study was 36 babies. This research was conducted at Puskesmas Bestari, Medan. Sampling using consecutive sampling. Collecting data using a FLACC scale questionnaire. Data analysis using paired t-test. The results showed that the effect of the 5S method on the pain response of infants aged 2-6 months during pentavalent immunization was shown by the statistical t-test with p = 0.007 and significantly reduced the pain response of infants at 15 seconds, second. 30, 45 seconds, and can reduce the length of crying babies after injection of pentavalent immunization. The results of this study are expected that nurses can use the 5 S method in relieving the pain response and the duration of crying in infants during immunization or when inserting sharp objects into the baby's body.